Efektivitas Strategi Promosi Kesehatan Rumah Sakit di Berbagai Wilayah : Systematic Literature Review - Widiar, Restu Prihandini; Najmi, Alfan (JURNAL KESEHATAN TERAPAN, 2025)
Hospital health promotion is an integral part of the healthcare system that plays a vital role in improving the quality of life of patients and the broader community. In various countries, hospitals not only serve as places for patient care but also act as health promotion centers responsible for disease prevention and enhancing public well-being through a variety of interventions and health education programs. This study aims to explore the effectiveness of health promotion strategies implemented in hospitals, focusing on patient empowerment, medical staff empowerment, the use of alternative therapies, and health communication. The method used is a systematic literature review of 15 relevant articles. The findings indicate that empowering patients and medical personnel can improve the quality of care and patient satisfaction. Patient empowerment that involves them in care decision- making enhances their experience, while medical staff empowerment through training improves their effectiveness in carrying out health promotion. The use of alternative therapies has been shown to provide additional benefits in enhancing patient well-being. The study also found that effective communication between medical staff and patients plays a crucial role in improving patient understanding, treatment adherence, and their involvement in care decision-making. The conclusion of this study is that approaches based on patient and medical staff empowerment, along with effective communication, are effective strategies for enhancing the quality of health promotion in hospitals. The implications of this research include the development of hospital policies that support better empowerment and communication between patients and medical staff.